The Horrible Sepulture of Mannes Resoun: Intoxication and Medieval English Felony Law - Elizabeth Papp Kamali (Rechtsgeschichte - Legal History, 2022)
The modern Anglo-American common law tends toward a hardline stance on intoxication, typically not treating it as an excuse to a criminal charge but offering a few well-guarded exceptions, most notably the idea in some jurisdictions that intoxication may be invoked to negate specific intent given its deleterious effect on cognitive capacity. A similar ambivalence toward the intersection of intoxication and criminal responsibility may be found in early English felony law, which offered no formal, intoxication-based exceptions to liability, but nevertheless countenanced jurors exercising their prudential judgment to treat intoxication as either an inculpatory or exculpatory factor in particular cases. Medieval English felony law treated drunkenness similarly to anger, recognizing that both conditions – which could be intertwined – often traced their roots to condemnable character formation and long-cultivated habit, and yet could result in a person’s detachment from their capacity to reason and exercise selfcontrol while under the influence. In the legal context, drunkenness was not equated with insanity, which was presumptively exculpatory, despite the fact that the two conditions could result in similar effects on a defendant’s observable behavior. Evidence from non-legal texts, including vernacular literature and guides for confessors, helps explain the concerns medieval English judges and jurors brought with them to the task of felony adjudication when faced with alcohol-laced facts, revealing a world in which tavern culture ensured alcohol’s omnipresence, but in which drunkenness was nevertheless not generally available as an excuse, partial or otherwise, for allegedly felonious behavior.